THE ROLE OF LAW IN THE CONCEPT THEORY OF JUSTICE TO REBUILD NATIONâ€™S ECONOMY IMPACT OF COVID-19 OUTBREAK IN INDONESIA - Faizah, Fikriya Afifiana (Wacana Hukum, 2021)
The role of law in This study aims to obtain information about the role of law inefforts to develop the country's economy due to the Covid-19outbreak in Indonesia which is reviewed based on Theory ofJustice. The research method used is statute approach, themethod of data collection through literature studies andqualitative normative data analysis techniques. The results of thestudy indicate that Indonesian government has takenextraordinary policies and steps in the context of saving thenational economy and financial system stability through variousrelaxation policies relating to the implementation of the StateBudget (APBN), especially by increasing spending on health,spending on social safety net, economic recovery, and strengthenthe authority of various institutions in the financial sector.However, an oversight of the implementation of the policy isneeded so that it is in accordance with the principles based onthe General Principles of Good Governance to create justice forequality before the law.. Â  Keywords: Role of Law, State Economy, Impact of COVID-19 outbreaks